Pengaruh Intellectual Capital Terhadap Kinerja Keuangan - Andini, Ayu; Samsiah, Siti; Azmi, Zul (Politeknik Raflesia Press, 2024)
The purpose of the study was to determine the effect of Intelectual Capital as measured using the VAICTM method which consists of three main elements, namely Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (SCVA) on financial performance proxied through Return On Asset (ROA). This research is quantitative research. The population used is technology companies listed on the Indonesia Stock Exchange, totaling 110 companies. Samples were taken and selected using purposive sampling technique so as to obtain a sample of 24 companies with 5 years of research, so that the number of observations obtained was 120. Research data obtained from the official website of the Indonesia Stock Exchange. The results of this study indicate that VACA and SCVA have a significant effect on Financial Performance (ROA) while VAHU and VAIC have no significant effect on Financial Performance (ROA). Keywords — Intellectual Capital, Value Added Intellectual Capital,Value Added Capital Employed, Value Added Human Capital , Structural Capital Value Added, Financial performance